PEMERIKSAAN PERKARA PERDATA SECARA PRODEO - Dian Latifiani (Qistie Jurnal Ilmu Hukum, 2012)
The purpose of  law  is  to protect  the public and provides  justice and harmony  in  the country,  besides  everyone  also  has  the  right  to  the  recognition,  guarantees, protection and legal certainty of fair and equal treatment before the law. In order to hold a judicial process that is fast, cheap, simple and open, it must be carried out regardless of  the position, group or  the social status of a person. In public  life, legal dispute among the community members can happen. If any conflict arises among the community, a lawsuit will show up. For the shake of the establishment of a harmonious community life, any lawsuit arising shall get a completion. The best  completion  is  by  implementing  deiberative  decision-making  to  reach consensus. However , if it does not succeed, in accordance with state law, the case should be  resolved  through  the court.Party  that  feels  his  or  her  right  has  been  violated, may  file  a  lawsuit  to  the competent court to adjudicate the case. The purpose of it is to get right protection as well as legal protection from the court. According to the principle of civil law, there  is cost  to  file a  lawsuit. This  is  in accordance with article 2 of paragraph 4 of the Law No. 48 of 2009 about  the Powers of  the Judiciary and article 121 of paragraph 4 HIR. However , for public members who are not able to pay for the lawsuit, should also get the same legal services, even societies like this may get legal assistance  to  litigate. One  form of  legal assistance  that can be given  to underprivileged communities in litigation of the civil case is: the allowance for litigating civil cases without cost (Prodeo). This is in accordance with the article 237 to 245 HIR that mention “those who are willing to be involved in law cases, either as plaintiffs or defendants, but they are unable to pay the cost, can litigate the  lawsuit with  the permission of not paying  the cost”.Keywords: Civil Casses, Prodeo,  Investigation.